PERAN INSTITUSI PENDIDIKAN DALAM PENGEMBANGAN NILAINILAI MORAL MELALUI SIKAP ILMIAH (SCIENTIFIC ATTITUDE) - Fathiyah, Kartika Nur Fathiyah (Paradigma, 2015)
Many complaints uttered concerning with the low ethics of students in the educational process, such as cheating in exams, data manipulation, plagiarism, and the phenomena of "˜jockeying’ (cheating in exams by taking the exam for the benefit of somebody else). These divergences need to be responded by always empowering all components involved in the educational institutions to hold high the scientific attitudes in every process of education. Scientific attitudes is firstly hold up by always motivating all components involved in educational institutions to develop and satisfy the curiosity which is naturally a basic trait of human beings. This curiosity will lead to fundamental scientific attitudes such as being honest in recording factual data, perseverant in accomplishing tasks, open to scientific truth, and always putting first priority to the truth obtained by means of scientific method, critical in responding to every proposition, statement or opinion, and creative while carrying out an experiment or research. Besides, the individual will always be consistent to use logic and reasoning in understanding and solving his/her problems. The responsibility coming in line with satisfying this curiosity will make the individual put aside all the dishonest and deceitful attitudes. That is why educational institutions are hoped to be the main sources of facilities for individuals to satisfy their curiosity, and to provide democratic, open, non-authoritarian and supporting educational atmosphere for individuals to perform scientific activities such as observation, experiment, and research. Also, educational institutions are expected to play an important role as a medium for reinforcement of the growth of academic attitudes as well as an agent of socialization for the community to generate academic attitudes, so that the community will eventually feel responsible to hold upright scientific attitudes. Key words : educational institution, value development, academic attitudes